Authority of The Prosperity of The Republic of Indonesia as Dominus Litis For the Crime of Illegal Logging - Vini Angeline; Cyrilus Iwan Santoso Rumangkang; Ngesty Handayani (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2023)
Forests in Indonesia are numerous and extensive, functioning as the lungs of the world, of course forests must be preserved. The number of cases of illegal logging (Illegal Logging) causes damage to forest ecosystems which can be detrimental to the state. Law Number 18 of 2013 Concerning the Prevention and Eradication of Forest Destruction has regulated criminal sanctions against anyone who commits Illegal Logging, the Attorney General of the Republic of Indonesia who holds the function of pre-prosecution and prosecution of criminal acts in Indonesia must continue to be fully involved in enforcing criminal law in Illegal logging. This research is a normative form of legal research using a statutory approach, a conceptual approach in order to achieve a prescriptive result and can be applied regarding Illegal Logging cases. One thing that distinguishes the science of law and the social sciences is that law is not included in the number of behavioral sciences. The conclusion is regulations regarding Illegal Logging need to be addressed. In general, it must be emphasized regarding the elements and intent of Illegal Logging itself. The prosecutor in exercising his authority in the pre-prosecution stage must also be reaffirmed in Law Number 18 of 2013 concerning the Prevention and Eradication of Forest Destruction.